NFV-TE: Uma Ferramenta para a Geração Automática de Funções Virtuais Rede para Engenharia de Tráfego - Quiles, Felipe Ribeiro; Moreira, João Vitor; Fulber-Garcia, Vinicius; Duarte Jr., Elias P. (Companion Proceedings of the Brazilian Symposium on Computer Networks and Distributed Systems (SBRC); 2022: Companion Proceedings of the 40th Brazilian Symposium on Computer Networks and Distributed Systems, 2022)
The unprecedented growth of computer and telecommunication networks has led to an extraordinary increase in network traffic. Traffic engineering consists of mechanisms related to monitoring, characterizing, modeling and controlling network traffic, in order to guarantee network performance. This work describes NFV-TE, a tool for generating virtual network functions for traffic engineering. The NFV (Network Function Virtualization) paradigm brings flexibility to networks by allowing the implementation of core functions on a software plane. After the network operator enters a set of features of the desired traffic engineering mechanism, NFV-TE validates and consolidates the data on a JSON configuration file, from which the corresponding virtual network function is generated. This paper describes various policers and shapers generated by NFV-TE, describing their execution in different scenarios and under different network traffic profiles.